2022
DOI: 10.3389/fcvm.2022.817705
|View full text |Cite
|
Sign up to set email alerts
|

Transcatheter Aortic Valve Implantation for Severe Bicuspid Aortic Stenosis – 2 Years Follow up Experience From India

Abstract: BackgroundTranscatheter aortic valve implantation (TAVI) is challenging in bicuspid aortic valve (BAV) anatomy. The patients are young, morphological phenotypes are many, calcium burden is high and there are technical challenges for best outcomes. Observational studies and registries are available with favorable data and experiences from around the world sharing methodologies and algorithms for sizing and implantation. We, therefore, analysed our data of procedural and in-hospital outcomes of TAVI in Bicuspid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 40 publications
1
2
0
Order By: Relevance
“…Encouraging data have been recently published in the STABILITY Registry which described a significant increase of the mean gradient at 4 years (13 ± 6.4 mmHg, p = 0.03) but very low rate of severe HVD (4%) and BVF (2%). 24 Similarly, Kumar et al 29 in India and Zhou et al 25 Like the BEAT Registry, we observed a higher rate of ≥moderate PVL in the SEV group at any timepoints evaluations, although this result was not statistically significant. However, in comparison to the BEAT findings, our prevalence of significant PVL at 1 year follow-up was similar for BEV devices (5.4% vs.…”
Section: Discussionsupporting
confidence: 44%
See 1 more Smart Citation
“…Encouraging data have been recently published in the STABILITY Registry which described a significant increase of the mean gradient at 4 years (13 ± 6.4 mmHg, p = 0.03) but very low rate of severe HVD (4%) and BVF (2%). 24 Similarly, Kumar et al 29 in India and Zhou et al 25 Like the BEAT Registry, we observed a higher rate of ≥moderate PVL in the SEV group at any timepoints evaluations, although this result was not statistically significant. However, in comparison to the BEAT findings, our prevalence of significant PVL at 1 year follow-up was similar for BEV devices (5.4% vs.…”
Section: Discussionsupporting
confidence: 44%
“…Encouraging data have been recently published in the STABILITY Registry which described a significant increase of the mean gradient at 4 years (13 ± 6.4 mmHg, p = 0.03) but very low rate of severe HVD (4%) and BVF (2%) 24 . Similarly, Kumar et al 29 in India and Zhou et al 25 in China reported sustained postprocedural hemodynamics improvements respectively up to 2 years and up to 3 years, without significant difference as compared to TAV patients.…”
Section: Discussionmentioning
confidence: 76%
“…That said, the 2-year results of TAVI in younger bicuspid patients in India have been comparable to the rest of the world. 5 With an aging population and increasing affordability, TAVI in India is set to become one of medicine's greatest triumphs.…”
mentioning
confidence: 99%